2018
DOI: 10.1016/j.combustflame.2018.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent flame propagation with pressure oscillation in the end gas region of confined combustion chamber equipped with different perforated plates

Abstract: Experiments were conducted in a newly designed constant volume combustion chamber with a perforated plate by varying the initial conditions. Hydrogen-air mixtures were used and the turbulent flame, shock wave, and the processes of flame-shock interactions were tracked via high-speed Schlieren photography. The effects of hole size and porosities on flame and shock wave propagation, intensity of the shock wave and pressure oscillation in closed combustion chamber were analyzed in detail. The effect of interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Kim et al [9] compared G-equation and well-stirred reactor (WSR) model in RANS simulation of a pre-chamber SI natural gas engine and the predictions with both combustion models are quite accurate. However, the combustion process in the dual-fuel pre-chamber engines is quite complicated and differs in pre-and main chambers, which is believed to include multiple combustion regimes such as non-premixed flame, jet flame and premixed flame propagation [19][20][21][22]. Consequently, it is very challenging to apply a single turbulent combustion model to accurately describe the entire combustion process for a dual-fuel pre-chamber engine in a cost-effective manner.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [9] compared G-equation and well-stirred reactor (WSR) model in RANS simulation of a pre-chamber SI natural gas engine and the predictions with both combustion models are quite accurate. However, the combustion process in the dual-fuel pre-chamber engines is quite complicated and differs in pre-and main chambers, which is believed to include multiple combustion regimes such as non-premixed flame, jet flame and premixed flame propagation [19][20][21][22]. Consequently, it is very challenging to apply a single turbulent combustion model to accurately describe the entire combustion process for a dual-fuel pre-chamber engine in a cost-effective manner.…”
Section: Introductionmentioning
confidence: 99%
“…Using the optical RCM, Wang et al [21] observed that the shock wave reflection at the wall initiates a detonation wave and they suggested that super-knock arises from the hotspot-induced deflagration to detonation transition followed by high-frequency pressure oscillation. In order to obtain clear observations of the pressure wave evolution in the confined space, Wei et al [22][23][24][25] conducted several experiments in a constant volume combustion chamber with Schlieren photography, wherein the shock wave formation and enhancement by the flame acceleration, as well as different combustion modes induced by the shock wave reflections, are all be captured. However, the complexity of the three-dimensional (3D) flow and limitations of measuring means make it difficult to reveal the underlying mechanism of autoignition induced by pressure wave reflections.…”
Section: Introductionmentioning
confidence: 99%
“…The use of grids or perforated plates in the turbulent combustion field gives many advantages. For example, it reduces the turbulent flame stabilization problems (lift-off) associated with the use of lean premixed flame in gas turbines and furnaces [1]. In experimental laboratory research, grids are applied to generate different levels of turbulence intensity and control integral length scales to study flame-turbulence interactions [2,3].…”
Section: Introductionmentioning
confidence: 99%